Evaluation of the plant growth promoting capacity of rhizobacteria of Algarrobo Neltuma pallida from dry forest of Piura – Perú, Laboratory and effect of seed germination - Jaramillo Calle, Liz Pamela; Merino-Rafael, Fernando Abilio (BOSQUE, 2024)
The main goal of this study is to isolate, select and determine the growth plant promoting ability of rhizobacteria in the stump and in the carob tree at the laboratory and seed level in order to have a bank of strains that can be used for the reforestation of the dry forest in Piura. Two composite samples of rhizosphere soil were obtained: one from stumps (felled trees) and the other from algarrobo trees, of which 16 and 18 bacterial strains were isolated, respectively. Measurements at a laboratory level included free nitrogen fixation, indolacetic acid, cellulolytic, and phosphate solubilizing production capacity. For each soil sample, five strains were selected with complementary (not antagonistic) properties to make an inoculating liquid and evaluate its effect on seed growth: 53 % for stumps, 37 % for trees, and 34 % for control (water). Inoculant strains were molecularly identified as Actinomycetes and other strains as Bacillus sp., B. paramycoides, B. wiedmannii, B. thuringiensis, and B. subtilis. Therefore, it was demonstrated that the rhizosphere of a dry forest carob, whether as a tree or stump, is an important source of rhizobacteria with plant-promoting capacity, which can be used to reforest the dry forest.